Co-adsorption of ciprofloxacin and Cu(II) onto titanate nanotubes: Speciation variation and metal-organic complexation - Xuming Xu; Yuxin Liu; Ting Wang; Ji, Haodong; Long Chen; Si Li; Liu, Wen (Journal of Molecular Liquids, 2019)
Titanate nanotubes (TNTs) have been reported to show good adsorption performance for heavy metals, but researches on organic contaminants adsorption by TNTs are limited. In this study, co-adsorption of a heavy metal (Cu) and an emerging organic contaminant (ciprofloxacin, CIP) by TNTs was investigated in binary systems. TNTs could simultaneously remove the two contaminants, with a high adsorption capacity of 234.5 μmol/g for Cu(II) and 237.0 μmol/g for CIP at pH 4 in the binary system. pH greatly affected adsorption due to speciation variation of the contaminants and surface charge change of TNTs. Cu(II)-CIP complexes dominated adsorption capacity and mechanism. Adsorption of CIP was promoted by high concentration of Cu(II) at pH 3–8 due to formation of abundant Cu(CIP±)2+, while inhibited by low concentration of Cu(II) because of competitive adsorption. The adsorption affinity of CIP species to TNTs was ranked as: Cu(CIP±)2+ > CIP+ > CIP± > Cu(CIP±)2+ > Cu(CIP−·CIP±)+ > CIP−. In comparison, the co-existence of CIP slightly affected Cu(II) adsorption considering the strong affinity of Cu2+ to TNTs. X-ray photoelectron spectrometer (XPS) and Fourier transform infrared spectroscopy (FTIR) results further confirmed the formation of Cu(II)-CIP complexes through –NH2Cu/–COOCu linkages. This work not only proposed a feasible technology for co-removal of heavy metals and organics from water, but also presented insight into interaction mechanisms of different contaminants with nanomaterials during adsorption.
Keywords: Adsorption; Complexation; Emerging organic contaminant; Heavy metal; Interaction mechanism; Titanate nanotubes